Analisis Kemampuan Manajerial Dosen dengan Prestasi Belajar Mahasiswa - Sri Larasati (Media Wisata, 2014)
This research aims to investigate the influence of the lecturers’ conceptual skills, the lecturers’ interpersonal skills, and the lecturers’ technical skills on the students’ learning achievement. The sample was the students of the Administration Hotel program study. The result of the t-test using SPSS 17 for all of the independent variables (conceptual skill= 0.000, interpersonal skill= 0.001, and technical skill= 0.044) showed that hypothesis 1 was proven. It means that the lecturers’ conceptual skills, interpersonal skills, and technical skills influenced the students’ learning achievement. The result of the t-test was supported by the result of the F-test which was very significant (=0.000). The influence of the independent variables (X) on the dependent variable (Y) was 68.7%. The result of the t-test showed that hypothesis 2, where the lecturers’ conceptual skill influenced the students’ learning achievement significantly, was also proven.